Pengaruh Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Aparatur Sipil Negara Pada Kantor Dinas Pertanian Di Kabupaten Mamasa - Anton Ambasari; Rina Rina; hafipah hafipah (Jurnal Online Manajemen ELPEI, 2022)
The aims of this study were 1) to find out and analyze the influence of leadership on the performance of the State Civil Apparatus at the Agriculture Service Office in Mamasa Regency, 2) to find out and analyze the effect of motivation on the performance of State Civil Apparatuses at the Agriculture Service Office in Mamasa Regency, and 3) To know and analyze the influence of work discipline on the performance of the Civil State Apparatus at the Agriculture office in Mamasa Regency. The analytical method used in this study is method Multiple Regression analysis. The research data were obtained from the State Civil Apparatus of the Agriculture Service Office in Mamasa Regency. The research approach is a causal approach that is explanatory in nature. The results of this study indicate that: 1) Leadership has a positive and significant influence on the performance of the State Civil Apparatus at the Agriculture Service Office in Mamasa Regency, 2) Motivation gives a positive and significant influence on the performance of the State Civil Apparatus at the Agriculture Service Office in Mamasa Regency, and 3) Work discipline  has a positive and significant influence on the performance of the State Civil Apparatus at the Agriculture Service Office in Mamasa Regency.